School publishing in Spain, identity, political culture and context: Dalmau Carles-Pla Encyclopedia - Castillejo Cambra, Emilio (Historia y Memoria de la Educación, 2017)
This article makes a comparative analysis of the ideological contents (identity, political culture, citizenship) of the editions of the Cyclic-Pedagogical Encyclopedia (intermediate level) of the Dalmau Carles-Pla publishing house in 1927 (Primo de Rivera’s dictatorship, although the draft still corresponds to the prior Restoration), 1936 (Second Republic) and 1953 (Franco’s regime). The outstanding ideological features of the 1927 edition are corporativism, elitism, a liberalism respectful of the historical constitution (Monarchy, Catholicism) and a Spanish patriotism compatible with the foralism and catalanism. Monarchism, Catholicism, corporativism, elitism, patriotism.... These are all values shared by Franco’s regime: the 1953 edition retains many of the previous texts although it introduces several modifications that serve to legitimize the Franco regime, root out the Catalonian nationalism and exalt Spanishheritage. The 1936 edition legitimizes the Republican legal framework, but as it preserves the corporativism, elitism, monarchism and Catholicism... from previous drafts, it does not legitimize Republican values such as freedom of conscience, secularism, social reformism.... This tells us something about the difficulties involved in altering the value system imposed by the oligarchy which established the liberal regime in Spain.